2020: A New Era of Sign Language Literature - Sutton, Valerie (Línguas & Letras, 2020)
<p style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; vertical-align: baseline;"> <table class="MsoNormalTable" style="border-collapse: collapse; border: none; mso-border-right-alt: solid windowtext .5pt; mso-yfti-tbllook: 1184; mso-padding-alt: 0cm 5.4pt 0cm 5.4pt;" border="1" cellspacing="0" cellpadding="0"> Summary: Sign language is the primary daily language of many Deaf people, yet sign language is not always included as a part of Deaf Education. Teachers of the Deaf in France in the late 1700s and early 1800s established using sign language in the classroom and yet generations later educators chose to revert back to oralism, not including any sign language when teaching Deaf children. And the trend continues to this day. Researchers in the 1960s, 70s and 80s proved that sign languages are natural languages, and yet this fact did not change the difficulties schools still have in reassuring parents and administrators that the Deaf students will learn to communicate, read and write a sign language as with your fellow listeners regarding oral languages that speak. Now, in the 21st century most educators and researchers are aware that sign languages are sophisticated languages with grammar, syntax and large vocabularies. Yet accepting sign languages as written languages has taken longer. Those who support the idea of writing sign languages feel that the availability of written literature and poetry in sign languages will lead to improved literacy in oral languages and in the long run, increase acceptance by the hearing world. Showing that sign languages have a written form helps establish sign languages as foreign languages in schools. With the advent of the internet and social media, writing sign languages is spreading quickly. The year 2020 is the beginning of a new era of sign language literature. Keywords: Sign Language; Literature; SignWriting; Deaf; Education. <p style="text-align: justify; line-height: 150%; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; vertical-align: baseline;">